Fate of trace organic compounds in the hyporheic zone: Influence of microbial metabolism. (1st October 2022) - Höhne, Anja; Müller, Birgit M.; Schulz, Hanna; Dara, Rebwar; Posselt, Malte; Lewandowski, Jörg; McCallum, James L.
Abstract: The hyporheic zone (HZ) is considered a hydrodynamically-driven bioreactor with significant pollutant removal capacities and can therefore not only improve wholestream water quality but also preserve human and ecosystem health. Microbial metabolism is hypothesized to play a key role in pollutant transformation in hyporheic sediments of natural streams. However, previous work investigating the influence of microbial metabolism on pollutant transformation has been predominantly laboratory studies. The key challenge for field studies is the appropriate determination of net microbial metabolism, i.e. information on the actual exposure times to specific microbial processes in the investigated system. The present study uses reactive fluorescent tracers to determine microbial metabolism and ultimately its influence on pollutant transformation, e.g. for trace organic compounds, in hyporheic sediments under natural conditions. In particular, the reactive fluorescent tracers resazurin and its main transformation product resorufin were used to determine the microbial metabolism of facultative or obligate aerobes. The influence of the derived microbial metabolism on the transformation of 20 trace organic compounds, such as pharmaceuticals, including 3 parent–daughter pairs, was examined. The present findings validate laboratory results on the microbially-mediated transformation of the anticonvulsant gabapentin to its main transformation product gabapentin lactam under natural conditions. All other TrOCs investigated did not show a clear link between TrOC reactivity to the microbial metabolism informed by the resazurin–resorufin-system. Overall, the present study not only demonstrates the use of the fluorescent tracer-system resazurin and resorufin for determining microbial metabolism of facultative or obligate aerobes but also generally highlights the potential of reactive fluorescent tracers to disentangle specific reactive properties and ultimately their influence on the fate of pollutants in natural HZs. Graphical abstract: Highlights: Microbial metabolism influences GAB-GPL transformation in natural hyporheic sediments. Fluorescent tracers inform exposure times to specific processes in natural systems. 2D-snapshot of pollutant and microbial reactivity in a natural streambed sediment. Approach for examining the influence of microbial metabolism on pollutant reactivity.